Reproductive Organ of Male Sulawesi Giant Rat (Paruromys dominator) - Ni Luh Putu Rischa Phadmacanty; R. Taufiq Purna Nugraha; Wirdateti . (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Abstract Indonesia has a biodiversity in fauna and one of them is the rat. The methodology to identify animal character is mostly based on morphological structure, the example of body lenght and hair color. However, reproductive organs of every species are diferent in location, shape, color and weight. Paruromys dominator is one of rats species in Sulawesi. Although, many informations about the rat's morphology is already provided , but no data about reproductive organ reported yet. Knowing, identifying and understanding the reproductive organs in that species must be done by sampling reproductive organs and measure all of them,. All of the reproductive organs were then collected for anatomical sample and processed for histological staining and were analyzed with light microscope and SEM. Based on the present study, Paruromys dominator has reproductive organs which are like other murids, namely seminal vesicle, testis, prostat glands, Cowper's glans and glans penis. There is no diference about histological stucture of rat's testis with other rats species, but based on the result of SEM, the penis has many penile spines. The sperm head is hook shape, it is like Rattus norvegicus. The average of head length and tail lenght of sperm are 1,28±0,101 μm and 12,95±1,139 μm, respectively.